UTILIZATION OF BOTTOM ASH AS MATERIAL MIXED SOIL LAYER BASICS IN HIGHWAY CONSTRUCTION - Muhammad Amir Wardana; Yasruddin Yasruddin (Universitas Lambung Mangkurat, 2017)
The use of coal as a power plant in the Asam-Asam produce residues such as bottom ash which cause environmental pollution. Therefore, research is conducted using bottom ash as a mixture of soil layer on the basis of the highway construction.This experiment is Atterberg Limit Testing, Testing Density, Sieve Analysis, hydrometer, compaction, and testing of CBR (California Bearing Ratio). In this study, using three types of combinations mixture of bottom ash, cement, and ground. Of the three combinations tested a whole has a high value of CBR and meet General Specifications, but the value of PI and Activity of the overall value combination does not meet specifications.The third combination can only be classified as ordinary soil embankment because of the three combinations all have a CBR value that meets specifications, but on the whole combination had PI values and the value of active that do not meet specifications. The combination can be regarded as an ordinary pile on condition combination is only used on the bottom of the heap or the backfilling that do not require the carrying capacity or high shear strength.Keywords: Bottom Ash, General Specifications, PI value, the value is On, the value of CBR.